Modeling and experiment of gas desorption of bubble column with an external loop in the heterogeneous flow regime - Im, Hanjin; Park, Jeil; Lee, Jae W. (The Korean journal of chemical engineering, 2019)
This work introduces an external loop to a bubble column and presents enhanced gas exchange in the heterogeneous flow regime. Gas exchange experiments under the same amount of gas input were carried out with varying gas velocity to understand the difference of bubble characteristic between the bubble column (BCR) and the bubble column with an external loop (BCR-EL). The observation of rise and descending velocity of bubbles in the BCR-EL showed that the fraction of bubbles passing the downcomer continuously increases with the incremental superficial gas velocity. A gas molecule in the liquid phase is desorbed by another gas molecule, and this gas exchange was assumed to be a phenomenon that a reactant in the liquid phase is converted to a product. To test the validity of the assumed gas exchange as a reaction in the experiments with the BCR-EL, a modeling study was performed using Fisher-Tropsch synthesis. It prevailed that the syngas conversion was higher in the BCR at the homogeneous flow regime, while the BCR-EL at the heterogeneous flow regime (above 0.08 m/s) had higher syngas conversion than the BCR due to higher gas recycle to the downcomer.